P129 Adoptive transfer of autologous cytotoxic T lymphocytes against epstein-barr virus (EBV-CTL) in patients with systemic lupus (SLE): preliminary results. (23rd March 2020) - Enfrein, Antoine; Clémenceau, Béatrice; Saiagh, Soraya; Vié, Henri; Hamidou, Mohamed
Abstract : Background: Patients with SLE show insufficient EBV control with an increased viral load and a decreased cytotoxic T-cell response associated with an abnormal humoral responses which theoretically may be pathogenic. In the present study we proposed an adoptive transfer of EBV-CTL to try to restore patients EBV specific T-cell control, and assess its effect on the humoral responses and the clinical status. Methods: Nine patients with SLE were enrolled in a Phase I/II clinical trial to receive autologous EBV-CTL (5.10 6 cells/kg). The frequency of EBV-specific T cells before and 10 days after injection was evaluated i) by ELISPOT directly on the peripheral blood mononuclear cells and ii) by estimation of IFN-γ, IL-2, TNF-α production and CD107 expression after pre-amplification of the EBV-specific precursors in vitro. We also monitored anti-VCA, anti-EAD, and anti-EBNA antibodies titers, EBV viral load, and clinical and biological disease activity parameters. Results: To date, 6 patients received EBV-CTL treatment. Ten days after injection, the EBV-CTL frequencies observed by ELISPOT increased moderately for 2 out of 3 patients tested. On the pre-amplified cells, increase in the production of IFN-γ after BLCL stimulation was observed for 4 out of 6 patients, and in the CD107 expression for 3 out of 6 patients. Serology titers remained stable during follow-up, with the exception of the anti-EBNA and anti-VCA IgG titers, which decreased in one patient. The viral EBV blood load did not vary significantly. Conclusions: The administration of EBV-CTL seems safe and well tolerated in SLE patients. Yet it might not be sufficient to improve the control of the virus by the host (and modify humoral response against EBV) despite a discreet increase in the EBV specific T-cell repertoire after injection. More data still need to be collected to precise the effects of the treatment on anti-EBV response and disease activity.